The Community Lab of Ideas for Health: Community-Based Transdisciplinary Solutions in a Malaria Elimination Trial in The Gambia - Masunaga, Yoriko; Jaiteh, Fatou; Manneh, Ebrima; Balen, Julie; Okebe, Joseph; D'Alessandro, Umberto; Nieto-Sanchez, Claudia; de Vries, Daniel H.; Gerrets, René; Peeters Grietens, Koen; Muela Ribera, Joan (Frontiers in Public Health, 2021)
Background: Community participation in global health interventions may improve outcomes and solve complex health issues. Although numerous community participatory approaches have been developed and introduced, there has been little focus on “how” and “who” to involve in the implementation of community-based clinical trials where unequal distribution of power between implementers and communities pre-exists. Addressing how to achieve community-based solutions in a malaria elimination trial in The Gambia, we developed the Community Lab of Ideas for Health (CLIH): a participatory approach that enabled communities to shape trial implementation. Methods: As part of transdisciplinary research, we conducted qualitative research with in-depth interviews, discussions, and observations in 17 villages in the North Bank Region of The Gambia between March 2016 and December 2017. We designed an iterative research process involving ethnography, stakeholder-analysis, participatory-discussions, and qualitative monitoring and evaluation, whereby each step guided the next. We drew upon ethnographic results and stakeholder-analysis to identify key-informants who became participants in study design and implementation. The participatory-discussions provided a co-creative space for sharing community-centric ideas to tackle trial implementation challenges. The proposed strategies for trial implementation were continuously refined and improved through our monitoring and evaluation. Results: The CLIH incorporated communities' insights, to co-create tailored trial implementation strategies including: village health workers prescribing and distributing antimalarial treatments; “compounds” as community-accepted treatment units; medicine distribution following compound micro-politics; and appropriate modes of health message delivery. Throughout the iterative research process, the researchers and communities set the common goal, namely to curtail the medical poverty trap by reducing malaria transmission and the burden thereof. This innovative collaborative process built trust among stakeholders and fully engaged researchers and communities in co-creation and co-implementation of the trial. Discussion: The CLIH approach succeeded in touching the local realities by incorporating a spectrum of perspectives from community-members and discerning project-derived knowledge from local-knowledge. This process allowed us to co-develop locally-oriented solutions and ultimately to co-establish an intervention structure that community-members were ready and willing to use, which resulted in high uptake of the intervention (92% adherence to treatment). Successfully, the CLIH contributed in bridging research and implementation.